QARDHUL HASAN'S CONTRACT AT ISLAMIC MICROFINANCE INSTITUTIONS: A MANAGEMENT AND EVALUATION STUDY - Alam, Azhar; Sidiq, Achmad Fajar; Nurrahman, Aditya (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This research details the Qardhul Hasan funding, administration, and assessment system. Six respondents were interviewed for this study, four from BMT Bina Umat Mandiri (managers, DPS members, secretaries, and customer service) and two from other customers. This research found that Qardhul Hasan is funded from Zakat, Infaq, Alms, Member Savings, and the Remaining Operating Results. Furthermore, most people who apply for this type of funding are in the education and trading sectors. Based on our analysis, the weaknesses of this financing lie in the distribution of human resources and the scarcity of available cash; To address these issues, we propose surveying consumers to collect reliable data and encourage individuals to save more proactively. Qardhul Hasan has a severe money shortage, but member savings are steadily growing and might help alleviate the crisis. While this funding can be used to serve others, oppose usury institutions, and please Allah. BMT Bina Umat Mandiri's follow-up plan involves employing member savings to create and enhance the quantity of cash for supporting Qardhul Hasan, expanding its reach in its mission to aid people. Management studies reveal that Qardhul Hasan funding at BMT Bina Umat Mandiri is not being redistributed to company capital but is being used to reduce the financial burden of healthcare and education on the local population.